2013
DOI: 10.4103/2230-8229.121998
|View full text |Cite
|
Sign up to set email alerts
|

Computer literacy of physicians among the hospitals of Makkah region

Abstract: Background and Objectives:A confidential inquiry by the Directorate General of Health Affairs, Makkah region, Saudi Arabia, found physicians in different hospitals were reluctant to enter patients’ related information in electronic medical record systems. One of the major issues raised was that they didn’t have the required computer literacy. Our aim, therefore, was to conduct a survey to highlight the computer literacy among the physicians of Makkah region.Materials and Methods:This cross-sectional survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…A study among nursing students in Australia has shown good competency in basic computer and information literacy skills; however, they were less competent in translating the skills in a clinical context [24]. Similarly, physicians in seven hospitals in KSA scored 80-90% on a 22-item questionnaire regarding their basic computer skills [25]. A cross-sectional study among a diverse group of healthcare professionals in five teaching hospitals in Iran has shown high scores of 83.9% and 80.6% on operational skills and information searching, respectively [26].…”
Section: Discussionmentioning
confidence: 99%
“…A study among nursing students in Australia has shown good competency in basic computer and information literacy skills; however, they were less competent in translating the skills in a clinical context [24]. Similarly, physicians in seven hospitals in KSA scored 80-90% on a 22-item questionnaire regarding their basic computer skills [25]. A cross-sectional study among a diverse group of healthcare professionals in five teaching hospitals in Iran has shown high scores of 83.9% and 80.6% on operational skills and information searching, respectively [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study conducted in Riyadh, KSA, showed that healthcare professionals lacked interest in EHR due to low computer literacy [2]. The findings related to computer skills inadequacy are also supported by Farooq & Shaker, who conducted a study with 451 physicians from seven hospitals in Makkah, KSA and concluded that participants required more training in even basic computer software such as Microsoft Word and PowerPoint [13].…”
Section: Introductionmentioning
confidence: 90%
“…2016;6(4):170-4. tion technologies, an increased application of new technologies in education leading to the development of new computer teaching aids is observed. [11][12][13] but to what extent these teaching aids have been utilised by the teachers specially the senior faculties needs to be assessed. There is a need to assess the scope of newer form of teaching aids in improving undergraduate medical teaching and identify the barriers to its use.…”
Section: Introductionmentioning
confidence: 99%